Penerepan Budaya Inovasi & Kreatifitas dengan Metode DMAIC dan Kaizen ( Continuous Improvement) pada PT. Indolakto Pasuruan - Yasman Yasman; Limgiani Limgiani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
A culture of innovation is very important to implement in a company to be able to maintain the existence and survival of the company. Successful innovation depends significantly on ability, skills and interpreting a rapidly changing environment. Apart from that, employee involvement also influences success in innovation. Innovation and creativity use the DMAIC (Define, Measure, Analyze, Improve and Control) method which is associated with KAIZEN in Japanese terms, which means